MECHANISMS OF CHRONIC PAIN AT OSTEOARTHROSIS OF THE KNEE - E. F. Turovskaya; L. I. Alekseeva; E. G. Filatova (Научно-практическая ревматология)
The main symptom of osteoarthritis (OA) is pain. Mechanisms of chronic pain in OA have not been fully investigated yet.Objective: to study key mechanisms of chronic pain in patients with knee OA.Subjects and methods. Authors examined 80 women aged 45–65 years, with chronic pain due to OA of the knee. Clinical rheumatologic and neurologic examinations, screening for neuropathic pain (PainDETECT and DN4 questionnaires), estimation of duration and intensity of pain, WOMAC assessment and evaluation of affective disorders (HADS questionnaire) were performed. X-ray and ultrasonography were used to assess destructive changes of theknee.Results. According to DN4 questionnaire, 25 (30%) patients scored 4 and more, i. e. had signs of neuropathic pain, whereas 55 (70%) did not (scored less than 4). Although neurologic examination did not reveal lesions of somatosensory system in neither of groups, assessment of the pain sensitivity showed hyperalgesia in 60% of cases. Patients with signs of neuropathic pain typically have secondary hyperalgesia propagating far from the damaged joint.Conclusion. 30% of patients with osteoarthritis have pain of different intensity determined by nociceptive and neuropathic mechanisms. At the same time the absence of lesions of somatosensory system does not let us to consider the pain neuropathic and indicates that it has dysfunctional nature. Signs of neuropathic pain associated with secondary hyperalgesia may be a clinical symptom of central sensitization. Due to this fact, reasonable therapy of osteoarthritis-associated chronic pain should include, besides NSAIDs, central acting drugs for neuropathic pain treatment.